2020
DOI: 10.1038/s41598-020-75657-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional in vivo and in vitro effects of 20q11.21 genetic aberrations on hPSC differentiation

Abstract: Human pluripotent stem cells (hPSCs) have promising therapeutic applications due to their infinite capacity for self-renewal and pluripotency. Genomic stability is imperative for the clinical use of hPSCs; however, copy number variation (CNV), especially recurrent CNV at 20q11.21, may contribute genomic instability of hPSCs. Furthermore, the effects of CNVs in hPSCs at the whole-transcriptome scale are poorly understood. This study aimed to examine the functional in vivo and in vitro effects of frequently dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 65 publications
(93 reference statements)
1
23
0
Order By: Relevance
“…This result is consistent with a recent study showing that human iPSCs with 20q11.21 CNV only have lesser commitment of the ectodermal lineage in teratoma with minor changes in the expression of genes in 20q11.21 loci 42 . Therefore, we propose that other cues to activate BCL2L1 promoter activity, such as YAP1 activation, would occur, leading to the acquisition of the survival advantage trait (e.g., YAP1 stabilization by Aurora A activity due to TPX2 induction).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with a recent study showing that human iPSCs with 20q11.21 CNV only have lesser commitment of the ectodermal lineage in teratoma with minor changes in the expression of genes in 20q11.21 loci 42 . Therefore, we propose that other cues to activate BCL2L1 promoter activity, such as YAP1 activation, would occur, leading to the acquisition of the survival advantage trait (e.g., YAP1 stabilization by Aurora A activity due to TPX2 induction).…”
Section: Discussionsupporting
confidence: 93%
“…The amplification of sub-chromosomal 20q11.21 has emerged as a frequent variant in culture-adapted hPSCs (9), a discovery propelled by advances in single-nucleotide resolution of genome-wide approaches. Considering that 25% of normal karyotype hESC lines, including hPSCs with early passage (14), and our cell models (Figs. 2 and 3) revealed a gain of 20q11.21 (9), it is likely hard to detect this minimal amplicon using conventional cytogenetic testing methods (i.e., spectral karyotyping and G-band karyotyping).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, BCL2L1 in 20q11.21 has been identified as a driver mutation for survival advantages in cultures (11, 12), which also results from an independent loss-of-function mutation in p53 (13). Other than the survival advantage conferred by the amplification of BCL2L1 or the TP53 mutation, the other genetic alterations have not been closely characterized, with a few notable exceptions (14), although various abnormal behaviors, such as tumor formation (15, 16) and impaired differentiation (17), in their progenies or hPSCs themselves were reported in animal models. Although CNV, including 20q11.21, occurs even in early passage (14, 18), the incidence of abnormal karyotypes may occur in a prolonged culture (19), suggesting that the induction of a set of gene(s) by CNV would lead to further chromosomal aberrations (20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the 20q11.21 locus contains cancer‐associated genes with potential oncogenic properties, and amplification detected in this region in colorectal cancer leads to genomic instability and recurrent genetic abnormalities and contributes to cancer pathogenesis 44,45 . Jo et al found that copy number variation in the 20q11.21 region led to increased migration capacities, metastatic potential, aberrant differentiation tendencies, cell proliferation, and decreased sensitivity to apoptosis in many types of cancers and human pluripotent stem cells 46 . Given the facts that miR‐1825 resides within 20q11.21 chromosomal region, where has been notified as a recurrent gain of function abnormality in human embryonic and induced pluripotent stem cells 13,14 and that 20q11.21 amplification in human embryonic stem cells resulted in acquisition of a gene‐expression signature enriched for cancer‐related genes, 16,17 we suggested that miR‐1825 might promote cellular phenotypes related to cancer progression in HNSCC as well.…”
Section: Discussionmentioning
confidence: 99%